Evie, the mist fairy - Meadows, Daisy; Ripper, Georgie (New York : Scholastic, 2004)
Evie, the mist fairy might have caused Wetherbury to get all fogged up by loosing her feather, and the weather fairies must bring back the good weather.
2.
006-009.
Keywords: Fairies -- Juvenile fiction; Feathers -- Juvenile fiction; Lost articles -- Juvenile fiction; Weather -- Juvenile fiction; Fairies -- Fiction; Feathers -- Fiction; Lost and found possessions -- Fiction; Weather -- Fiction; Fantasy fiction